Overview General The Relationship Between Parental Support and Children's Anxiety During Infusion Installation in The Children's Room at Hospital X - Kristina Mei Hariaty Siburian; Roza Indra Yeni; Rima Berlian Putri; Ricky Riyanto Iksan (Lembaga Penelitian dan Pengabdian Masyarakat, Stikes Panrita Husada Bulukumba, 2026)
Background: Child anxiety during medical procedures, such as intravenous (IV) insertion, is a common issue that can affect both comfort and the success of the procedure. Parental support plays a crucial role in helping children manage this anxiety. This study aimed to examine the relationship between parental support and the level of child anxiety during IV insertion in the Pediatric Ward of Ciputra Hospital Citra Garden City. This study employed an analytic quantitative design with a cross-sectional approach. The population consisted of 67 respondents, and the sample included 67 children undergoing IV insertion along with their accompanying parents, selected using a total sampling technique. Data were collected using questionnaires to measure parental support and the children’s anxiety levels. Data analysis was performed using the Chi-Square test to determine the relationship between parental support and child anxiety levels. The results showed that most respondents received high parental support, with 52 respondents (77.6%). Statistical analysis indicated a significant relationship between parental support and the children’s anxiety levels (p = 0.032). The study concludes that parental support is an important factor in reducing child anxiety during medical procedures. These findings can serve as a basis for healthcare professionals to actively involve parents in child care and as a reference for developing family education programs focused on managing child anxiety.